INTEGRATING MODERN PEDAGOGICAL TECHNOLOGIES TO ENHANCE ART LITERACY IN SECONDARY EDUCATION - Bobomurodova Sojida Ablakulovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article examines the integration of modern pedagogical technologies into art education to enhance students’ art literacy and creative competencies. It explores how digital tools, flipped classroom models, and interactive learning methods can enrich students’ understanding of visual culture and artistic expression. The paper argues that technology-based approaches not only make art learning more engaging but also foster analytical, critical, and compositional thinking skills among students.